2004
DOI: 10.1021/jf049656s
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Omega-3 Fatty Acids in Fortified Surimi Seafoods during Chilled Storage

Abstract: Physical, chemical and sensory properties of cooked surimi seafood gels (crab analog) fortified with omega-3 fatty acids (FA) were monitored during chilled storage. Three sources of stabilized omega-3 FA (fish oil concentrate, menhaden oil, and a purified marine oil) were each incorporated into gels to an omega-3 FA content of 1.5% or 2.5%, wt/wt. Omega-3 FA stability, development of off-flavors, and changes in color and texture were monitored during chilled storage for two months. Gels with fish oil concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
44
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 20 publications
4
44
0
Order By: Relevance
“…Shear strain generally confirmed cohesiveness determined with texture profile analysis (TPA) ( Table 4). Pérez-Mateos et al (2004) reported similar results for gels with menhaden oil. Kramer shear force values confirmed (P > 0.05) torsion shear stress, except gels with blend oil which had slightly higher (P < 0.05) Kramer shear force (Fig.…”
Section: Texture Properties Of Heat-set Surimi Gelsmentioning
confidence: 53%
See 2 more Smart Citations
“…Shear strain generally confirmed cohesiveness determined with texture profile analysis (TPA) ( Table 4). Pérez-Mateos et al (2004) reported similar results for gels with menhaden oil. Kramer shear force values confirmed (P > 0.05) torsion shear stress, except gels with blend oil which had slightly higher (P < 0.05) Kramer shear force (Fig.…”
Section: Texture Properties Of Heat-set Surimi Gelsmentioning
confidence: 53%
“…The crab flavour was a water-miscible liquid. The above levels of functional additives were found in previous studies as optimal for gelation of fish muscle protein and consequently texture development as well as closely resembling commercial surimi-based seafood products (Chen & Jaczynski, 2007a,b;Pérez-Mateos, Boyd, and Lanier, 2004;Pérez-Mateos, Lanier, and Boyd, 2006;Taskaya, Chen, Beamer, and Jaczynski, 2009;Taskaya, Chen, and Jaczynski, 2009;. Thus, the following x-3 PUFA-rich oils were added to surimi paste: (1) corn oil was obtained from a local, chain grocery supermarket (The Kroger Co., Cincinatti, OH), (2) flaxseed oil was obtained from Jedwards International Inc. (Quincy, MA), (3) algae oil (DHAS) was obtained from Martek Biosciences (Columbia, MD), (4) menhaden oil (Omega Pure 8042TE) was obtained from Omega Pure (Reedsville, VA), (5) krill oil (4225F) was obtained from Enzymotec USA Inc. (Springfield, NJ) and (5) blend (Flaxseed:Algae:Krill, 8:1:1).…”
Section: Preparation Of Surimi Pastementioning
confidence: 55%
See 1 more Smart Citation
“…Crabflavored surimi seafood typically contains crab flavor. Watersoluble crab flavor (F-11019, Activ International, Mitry-Mory Cedex, France) was added to the surimi paste at 3.7 g/100 g (Perez-Mateos, Boyd, & Lanier, 2004). Surimi paste with added ice, SiO 2 , and crab flavor was mixed in the universal food processor (Model UMC5, Stephan Machinery Corp., Columbus, OH) at low speed for 1 min.…”
Section: Preparation Of Surimi Gelsmentioning
confidence: 99%
“…The above levels of functional additives were found in previous studies as optimal for gelation of fish muscle protein isolate and consequently texture development as well as closely resembling commercial surimi-based seafood products (Park, 2005;Perez-Mateos, Boyd, & Lanier, 2004;Taskaya, Chen, & Jaczynski, 2010). A 0.5 g/100 g of titanium dioxide (TiO 2 ) [Titanium (IV) oxide, SigmaeAldrich, Inc., St. Louis, MO] was also added to the paste (Tahergorabi et al, 2011a.…”
Section: Preparation Of Fish Protein Pastementioning
confidence: 99%